2016
DOI: 10.1186/s12888-016-0960-0
|View full text |Cite
|
Sign up to set email alerts
|

Reasons for living and hope as the protective factors against suicidality in Chinese patients with depression: a cross sectional study

Abstract: BackgroundThe risk factors of suicidal ideation and attempts have been discussed in many researches. Few studies have examined reasons for living and hope as protective factors against suicide in a clinical population. It is unclear if these factors help to reduce suicide rates in patients with depression. The study aimed to assess the role of reasons for living and hope in the identification and reduction of suicidality and explore the influence of reasons for living or hope in the transition from suicidal id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0
11

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 46 publications
2
34
0
11
Order By: Relevance
“…These studies have indicated that negative individual (e.g., hopelessness) and social (e.g., isolation) factors can contribute to the risk of suicidal ideation of older adults. Recently, with the emergence of positive psychology, which has been defined as the scientific study of optimal human functioning [10], an increasing number of researchers has shifted their focus from passive influential factors to the effect of positive factors [11].…”
Section: Introductionmentioning
confidence: 99%
“…These studies have indicated that negative individual (e.g., hopelessness) and social (e.g., isolation) factors can contribute to the risk of suicidal ideation of older adults. Recently, with the emergence of positive psychology, which has been defined as the scientific study of optimal human functioning [10], an increasing number of researchers has shifted their focus from passive influential factors to the effect of positive factors [11].…”
Section: Introductionmentioning
confidence: 99%
“…Researchers found that meaning in life is related to students' well-being (Dogra, Basu, & Das, 2011), life satisfaction (Park, Park, & Peterson, 2010), and hope (Vela, Lerma, et al ., 2014) . Finally, hope is a future-oriented attitude that helps individuals manage crisis situations by projecting positive thoughts toward the future (Luo, Wang, Wang, & Cai, 2016) . According to Sears and Kraus (2009), hope provides a sense of goal-directed determination and ability to generate plans to achieve goals .…”
Section: Positive Psychology Factorsmentioning
confidence: 99%
“…Hope is a future‐oriented perspective that helps adolescents project positive thoughts toward the future (Luo, Wang, Wang, & Cai, 2016) and is an essential factor in humanistic counseling due to the positive relationship with goal attainment (Feldman, Rand, & Kahle‐Wrobleski, 2009), future academic achievement, mental health (Marques, Pais‐Ribeiro, & Lopez, 2011), and meaning in life (Vela, Lu, et al, 2015). In addition, hope provides adolescents with a goal‐directed determination that helps them generate plans for desired goals (Sears & Kraus, 2009).…”
Section: Humanistic Factorsmentioning
confidence: 99%